2015
DOI: 10.1155/2015/941265
|View full text |Cite
|
Sign up to set email alerts
|

Custom-Made Computer-Aided-Design/Computer-Aided-Manufacturing Biphasic Calcium-Phosphate Scaffold for Augmentation of an Atrophic Mandibular Anterior Ridge

Abstract: This report documents the clinical, radiographic, and histologic outcome of a custom-made computer-aided-design/computer-aided-manufactured (CAD/CAM) scaffold used for the alveolar ridge augmentation of a severely atrophic anterior mandible. Computed tomographic (CT) images of an atrophic anterior mandible were acquired and modified into a 3-dimensional (3D) reconstruction model; this was transferred to a CAD program, where a custom-made scaffold was designed. CAM software generated a set of tool-paths for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Nowadays, modern digital technologies allow the surgeon to virtually design and then fabricate custom-made synthetic porous scaffolds, for use in bone reconstructive procedures [20, 2326, 36]. In different medical fields, several studies have demonstrated that the combination of modern image acquisition techniques with 3D reconstruction software allows the clinician to obtain custom-made scaffolds for the regeneration of bone structures [20, 2326, 3640].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nowadays, modern digital technologies allow the surgeon to virtually design and then fabricate custom-made synthetic porous scaffolds, for use in bone reconstructive procedures [20, 2326, 36]. In different medical fields, several studies have demonstrated that the combination of modern image acquisition techniques with 3D reconstruction software allows the clinician to obtain custom-made scaffolds for the regeneration of bone structures [20, 2326, 3640].…”
Section: Discussionmentioning
confidence: 99%
“…In different medical fields, several studies have demonstrated that the combination of modern image acquisition techniques with 3D reconstruction software allows the clinician to obtain custom-made scaffolds for the regeneration of bone structures [20, 2326, 3640]. This powerful combination allows the surgeon to virtually plan the reconstruction of an atrophic bone area on his/her computer and to fabricate a custom-made biocompatible scaffold designing its size, thickness, and shape [20, 2326, 3640]. The fabrication of the scaffold can be obtained by milling blocks of synthetic bone substitutes that mimic the structure of natural bone and therefore promote the formation of new bone when implanted in the area of defect [3640].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations